Efficacious bioremediation of heavy metals and radionuclides from wastewater employing aquatic macro‐ and microphytes - Das, Swati; Das, Sovik; Ghangrekar, Makarand M. (Journal of basic microbiology, 2022)
Cytotoxic, mutagenic, and carcinogenic contaminants, such as heavy metals and radionuclides, have become an alarming environmental concern globally, especially for developed and developing nations. Moreover, inefficient prevalent wastewater treatment technologies combined with increased industrial activity and modernization has led to increase in the concentration of toxic metals and radioactive components in the natural water bodies. However, for the improvement of ecosystem of rivers, lakes, and other water sources different physicochemical methods such as membrane filtration, reverse osmosis, activated carbon adsorption, electrocoagulation, and other electrochemical treatment are employed, which are uneconomical and insufficient for the complete abatement of these emerging pollutants. Therefore, the application of bioremediation employing aquatic macrophytes and microphytes have gained considerable importance owing to the benefits of cost‐effectiveness, eco‐friendly, and higher energy efficiency. Thus, the present review aims to enlighten the readers on the potential application of algae, cyanobacteria, plant, and other aquatic micro‐ and macrophytes for the elimination of carcinogenic metals and radioactive isotopes from wastewater. Additionally, the use of transgenic plants, genetically modified species, algal–bacterial symbiosis for the enhancement of removal efficiency of mutagenic contaminants are also highlighted. Furthermore, species selection based on robustness, mechanism of different pathways for heavy metal and radionuclide detoxification are elucidated in this review article.